Comparison of dynamic muscle activation during fente execution in fencing between wearing weighted and waterbag vests - Lee, J. Y.; Lee, C. K.; Kang, S.; Park, I. B. (Korean Journal of Sport Biomechanics, 2023)
Objective: This study aimed to compare the activity of the trunk and leg muscles while performing fente (in fencing) wearing weighted and waterbag vests. Method: The electromyography test was used to measure and analyze the activation of the trunk and leg muscles. Eight active fencers from B University (age: 19.5 ± 0.66 years, height: 179.75 ± 5.93 cm, weight: 72 ± 6.32 kg) were selected for this study. Results: According to the EMG analysis results of the 4 muscles measured in this study, left-right differences were observed for rectus abdominis and external oblique abdominis, but left-right differences between the groups were not significant. The gluteus medius muscle was not significantly different from the adductor muscle, but there were significant differences between the groups. Conclusion: The electromyographic analysis of the four muscles measured in this study revealed no significant difference between the left and right recti abdominis and external obliques depending on the vests. However, significant differences were observed between the left and right gluteus medius and adductor longus. Our results can be interpreted as the effects of the inherent movements involved in the fente. Furthermore, our results indicate that the weight transfer while wearing a waterbag vest, which provides an unstable environment, increased the activity of leg muscles.